Cu Nanowire Networks with Well-Defined Geometrical Parameters for Catalytic Electrochemical CO2 Reduction - Ulrich, Nils; Schäfer, Michelle; Römer, Melina; Straub, Sascha Dominic; Zhang, Siyuan; Brötz, Joachim; Trautmann, Christina; Scheu, Christina; Etzold, Bastian J.M.; Toimil-Molares, Maria Eugenia (ACS Applied Nano Materials, 2023)
Three-dimensional, highly interconnected copper nanowire networks are designed and fabricated by electrodeposition in etched ion track polymer templates with interconnected nanochannels and subsequently applied as a catalyst for the electrochemical CO2 reduction toward hydrocarbons and alcohols in an aqueous electrolyte. The specific surface area expressed by the nanowire networks can be adjusted by tailoring the wire length, wire diameter, and nanowire number density to values between 70 cm2 and 300 cm2 per cm2 geometrical sample area. The conversion efficiency and selectivity of CO2 reduction toward liquid- and gas-phase products are studied as a function of the applied potential. Before and after the CO2 reduction reaction, the nanowire networks are characterized by scanning and transmission electron microscopy and by X-ray diffraction, evidencing their stability during CO2 reduction in a potential region between −0.5 V and −0.93 V versus RHE.
CRIS-Team Scopus Importer:2023-08-15
Keywords: copper nanowire networks; electro catalyst; electrochemical CO; electrosynthesis; ion-track nanotechnology